Hematological and Biochemical Abnormalities in Pregnancy-Induced Hypertension - Amulya Boddapati; Renuka Inuganti Venkata; Parveen Riyaz; Vydehi B.V; Vamshi Deepak (Golestan University Of Medical Sciences, 2022)
Background and objectives: Pregnancy-induced hypertension (PIH) is a serious pregnancy complication that contributes significantly to both maternal and neonatal morbidity and mortality. The study aimed to evaluate various hematological parameters associated with PIH and to identify early hematological parameters predictive of eclampsia and hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome. Methods: A total of 114 subjects were studied. Venous blood samples were collected to study hematological profile, including coagulation and biochemical analysis. Results: Of 114 subjects, 35 were categorized as gestational hypertension, 33 as mild preeclampsia, 40 as severe preeclampsia, and six as eclampsia. Eight cases progressed to HELLP syndrome. The mean hemoglobin level was 10.6+2.1 g/dl, which decreased significantly in PIH patients as the disease progressed (p=0.045). The mean platelet count was 191 + 84 x 109cells/L. The mean platelet count in PIH patients decreased significantly with disease progression (p=0.008). The mean prothrombin time and activated partial thromboplastin time were 13.12 + 1.33 and 33.62 + 6.34 seconds, respectively. These parameters also increased significantly with disease progression (p<0.05). Liver enzymes, creatinine, and uric acid levels increased significantly as the disease progressed (p<0.05). Conclusion: Most of the hematological parameters changed as PIH progressed in severity. The mean levels of hemoglobin, platelet, and lymphocytes are lower in cases with PIH, while the mean prothrombin time and activated partial thromboplastin time are higher in these patients. These variables are sensitive and specific prognostic markers for patients with PIH.